Hexahexyloxycalix[6]arene, a Conformationally Adaptive Host for the Complexation of Linear and Branched Alkylammonium Guests - Veronica Iuliano; Carmen Talotta; Paolo Della Sala; Margherita De Rosa; Annunziata Soriente; Placido Neri; Carmine Gaeta (Molecules, 2023)
Hexahexyloxycalix[6]arene 2b leads to the endo-cavity complexation of linear and branched alkylammonium guests showing a conformational adaptive behavior in CDCl3 solution. Linear n-pentylammonium guest 6a+ induces the cone conformation of 2b at the expense of the 1,2,3-alternate, which is the most abundant conformer of 2b in the absence of a guest. In a different way, branched alkylammonium guests, such as tert-butylammonium 6b+ and isopropylammonium 6c+, select the 1,2,3-alternate as the favored 2b conformation (6b+/6c+⊂2b1,2,3-alt), but other complexes in which 2b adopts different conformations, namely, 6b+/6c+⊂2bcone, 6b+/6c+⊂2bpaco, and 6b+/6c+⊂2b1,2-alt, have also been revealed. Binding constant values determined via NMR experiments indicated that the 1,2,3-alternate was the best-fitting 2b conformation for the complexation of branched alkylammonium guests, followed by cone > paco > 1,2-alt. Our NCI and NBO calculations suggest that the H-bonding interactions (+N–H···O) between the ammonium group of the guest and the oxygen atoms of calixarene 2b are the main determinants of the stability order of the four complexes. These interactions are weakened by increasing the guest steric encumbrance, thus leading to a lower binding affinity. Two stabilizing H-bonds are possible with the 1,2,3-alt- and cone-2b conformations, whereas only one H-bond is possible with the other paco- and 1,2-alt-2b stereoisomers.